Influence of nitrogen fertilizer on resistance to fall armyworm (Lepidoptera: Noctuidae) in tropical Honduran landrace dorghum - Lopez, J.=700 1 Pitre, H.N.; Meckentock, D.H.
(Es, En)
Ilus., 24 ref.
Keywords: SORGHUM BICOLOR; SPODOPTERA FRUGIPERDA; INSECTA; DESARROLLO BIOLOGICO; ANTIBIOSIS; ESTADO NUTRICIONAL; HONDURAS